Review of Joanna Demers. 2010. Listening Through the Noise: The Aesthetics of Experimental Electronic Music. Oxford, UK: Oxford University Press. Nick Collins and Julio d’Escriván. 2007. The Cambridge Companion to Electronic Music. Cambridge, UK: Cambridg - Polymeropoulou, Marilou (Current Musicology, 2010)
In Listening Through the Noise, Demers presents an aesthetic theory of experimental electronic music accompanied by audio examples which can be found online. In The Cambridge Companion to Electronic Music (CCTEM), electronic music and technology’s influence on 20th and 21st century music making is discussed, as well as how the history of electronic music is based on perspectives by composers and scholars from a variety of disciplines, including communication studies, musicology, visual arts, music technology, psychology of music, and computer science. Both books define electronic music as organized sounds generated by electronic circuits, which may be part of musical instruments, computers, or nay electronic equipment. Taken together, the Listening Through the Noise, and the CCTEM can be used to understand many different approaches, problems, questions, and aims regarding electronic music in a social, cultural and historical context, while also addressing its standing point in music.